Self-corrosion rate evaluation device for anode material of metal-air battery
By designing a self-corrosion rate evaluation device for metal-air batteries, using air collecting funnel and alkaline burets to collect hydrogen, the problem that the existing technology cannot effectively quantify the anode self-corrosion hydrogen analysis rate is solved, and a more accurate self-corrosion rate is achieved Calculate.
Patent Information
- Application Number
- CN202420633524.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2034-03-28
AI Technical Summary
The prior art cannot effectively quantify the self-corrosion hydrogen analysis rate of the anode during discharge and its impact on utilization efficiency and discharge performance of metal-air batteries.
A self-corrosion rate evaluation device for metal-air battery anode material is designed, including a detection container, an air collection funnel and a support. Hydrogen gas is collected through the air collection funnel and liquid level changes are recorded using an alkaline buret tube to calculate the hydrogen evolution rate.
The device can collect hydrogen without affecting the discharge process and provide more accurate data support, improving the stability and accuracy of hydrogen collection, thereby calculating the self-corrosion rate of the metal anode.
Smart Images

Figure CN222166698U_ABST
Abstract
Description
Technical Field
[0001] The utility model belongs to the research field of discharge performance of metal-air batteries and relates to a self-corrosion rate evaluation device for anode materials of metal-air batteries. Background Art
[0002] Metal-air batteries are batteries that use metals with relatively negative electrode potentials, such as magnesium, aluminum, zinc, mercury, and iron, as anodes and oxygen in the air or pure oxygen as cathode active materials. During the discharge process of the anode metal material, some electrons are discharged as electrons in the circuit, while the other part of the electrons are absorbed by water and release hydrogen, causing self-corrosion of the metal material. The self-corrosion of the anode metal material during the discharge process due to hydrogen evolution will seriously affect the anode utilization efficiency of the metal anode, thereby affecting the discharge performance of the metal-air battery.
[0003] However, existing research on the corrosion rate of metal-air batteries usually uses the immersion hydrogen evolution method, which can well evaluate the corrosion performance of metal materials, but cannot reasonably evaluate the metal self-corrosion during the discharge process, and thus cannot effectively quantify the self-corrosion hydrogen evolution rate of the metal anode during the discharge process, and its impact on the anode utilization efficiency and discharge performance. Utility Model Content
[0004] In view of this, the purpose of the utility model is to provide a self-corrosion rate evaluation device for anode materials of metal-air batteries, so as to collect hydrogen during the discharge process and thereby obtain the hydrogen evolution rate of the anode metal alloy, thereby providing more reasonable data support for evaluating the self-corrosion rate of the anode of the metal-air battery during the discharge process.
[0005] To achieve the above-mentioned purpose, the utility model provides a self-corrosion rate evaluation device for a metal-air battery anode material, comprising a detection container, in which a sample to be tested is placed, a first opening connected to the outside is opened on the wall of the detection container at a position corresponding to the position of the sample to be tested, and an air cathode sheet is arranged on the outer wall of the detection container in a manner of covering the first opening.
[0006] The device also includes a gas collecting funnel inverted above the sample to be tested, a conical cut is opened on the side of the gas collecting funnel corresponding to the first opening position, and a diaphragm is covered on the conical cut. Preferably, the cross-sectional shape of the conical cut is a hyperbolic cross-section perpendicular to the width direction of the detection container.
[0007] Optionally, the detection container is a box with an opening on the top, the first opening is provided on one of the side surfaces of the detection container, the side surface provided with the first opening is a first end surface, and the air cathode sheet is provided outside the first end surface.
[0008] The device also includes a clamping plate with an adjustable distance from the first end surface, the air cathode sheet is arranged between the clamping plate and the first end surface and abuts against the two, and a second opening is provided on the clamping plate at a position opposite to the first opening, connecting the air cathode sheet and the outside. The second opening is arranged at the center of the clamping plate, and its size is the same as the first opening.
[0009] The device also includes a support detachably mounted inside the detection container, and the sample to be tested is placed in the detection container through the support, wherein the support includes a clamping portion, and the clamping portion has a through hole to accommodate the sample to be tested.
[0010] Optionally, the support also includes a strip seat extending along the length direction of the first end face, the clamping portion is fixed on the strip seat, and at least one boss is fixed on the strip seat, the boss extends along the width direction of the container to be tested to form a placement platform for placing the gas collecting funnel. Preferably, two bosses are fixed on the strip seat, and the two bosses are respectively located on both sides of the clamping portion.
[0011] Optionally, a limiting groove is provided on the boss, and the edge of the gas collecting funnel is embedded in the limiting groove.
[0012] Optionally, two assembly keys are vertically arranged at two ends of the strip seat, and assembly grooves matching with the assembly keys are arranged on the inner walls of the first side surface and the second side surface of the detection container adjacent to the first end surface.
[0013] Optionally, two bosses are fixedly provided on the strip seat, and the two bosses are respectively arranged between the clamping portion and the two assembly keys.
[0014] Optionally, a connecting block is fixed on the first side surface and the second side surface adjacent to the first end face, two connecting screws pass through the clamping plate and the connecting block, four fastening nuts are installed in groups of two at both ends of each connecting screw, and the distance between the clamping plate and the first end face is adjusted by adjusting the position of the fastening nuts on the connecting screws.
[0015] Optionally, the gas collecting funnel includes a gas collecting part and a gas guiding part which are connected to each other, the gas collecting part is a cone, and the gas guiding part is a column.
[0016] Optionally, the gas collecting funnel is inverted on the support, and the edge of the gas collecting part thereof is embedded in the limiting groove of the support.
[0017] Optionally, during the discharge process, an alkali burette is connected to the outlet end of the gas guide portion, and the liquid level change of the alkali burette is the hydrogen evolution data of the sample to be tested.
[0018] The beneficial effects of the utility model are:
[0019] The utility model provides a self-corrosion rate evaluation device for anode materials of a metal-air battery. A gas collecting funnel is arranged above the sample to be tested, and a conical cutout is arranged on the side of the gas collecting funnel facing the air cathode sheet, and a diaphragm is covered on the conical cutout to allow the ions involved in the reaction to pass freely between the metal anode and the air cathode sheet, while preventing the hydrogen precipitated by the metal anode due to self-corrosion from overflowing the gas collecting funnel, thereby collecting hydrogen without affecting the discharge process, and providing more reasonable data support for evaluating the self-corrosion rate of the anode of the metal-air battery during the discharge process. In addition, the utility model covers the gas collecting funnel above the sample to be tested, and arranges a boss and a limit groove on the support carrying the sample to be tested, so that the gas collecting funnel always stably covers the sample to be tested during the discharge process, thereby improving the stability and accuracy of hydrogen collection, and further ensuring the accuracy of the self-corrosion rate of the metal anode.
[0020] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and will be apparent to those skilled in the art based on the following examination and research, or can be taught from the practice of the present invention to some extent. The objectives and other advantages of the present invention can be achieved and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solution and advantages of the utility model clearer, the utility model will be described in detail below in conjunction with the accompanying drawings, in which:
[0022] Figure 1 This is one of the structural schematic diagrams of the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model;
[0023] Figure 2 The second structural schematic diagram of the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model;
[0024] Figure 3 The third structural schematic diagram of the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model;
[0025] Figure 4 The fourth structural schematic diagram of the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model;
[0026] Figure 5 A schematic diagram of the structure of the gas collecting funnel and the support of the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model;
[0027] Figure 6The self-corrosion rate of the cast Mg-0.6%Gd alloy at 10mA cm-2 was obtained by using the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model. -2 The hydrogen evolution results of discharge for 180 min at the current density;
[0028] Figure 7 The self-corrosion rate of the extruded Mg-0.6%Gd alloy at 10mA cm-2 obtained by using the self-corrosion rate evaluation device for the metal-air battery anode material provided by the utility model -2 Hydrogen evolution results after discharge for 360 min at the current density.
[0029] Reference numerals:
[0030] 100-detection container; 110-clamping plate; 111-connecting screw; 112-fastening nut; 113-second opening; 120-support; 121-assembly key; 122-limiting groove; 123-boss; 124-clamping portion; 125-strip seat; 130-assembly groove; 140-first end face; 141-first opening; 150-second end face; 160-first side face; 170-second side face; 180-connecting block; 200-gas collecting funnel; 210-conical cut; 220-diaphragm; 300-sample to be tested; 400-air cathode sheet. DETAILED DESCRIPTION
[0031] The following describes the implementation of the present invention through specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner. The following embodiments and the features in the embodiments can be combined with each other without conflict.
[0032] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present utility model. In order to better illustrate the embodiments of the present utility model, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0033] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "back" and the like indicate directions or positional relationships, they are based on the directions or positional relationships shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0034] See also Figure 1 to Figure 5 The utility model provides a self-corrosion rate evaluation device for a metal-air battery anode material, which collects hydrogen during the discharge process and improves the accuracy of the hydrogen collection results, thereby more accurately measuring the hydrogen evolution rate of the metal alloy and providing more reasonable data support for evaluating the self-corrosion rate of the anode of the metal-air battery during the discharge process.
[0035] like Figure 1 , Figure 2 As shown, the evaluation device includes a detection container 100, which is a box with an open top and has four side surfaces and a bottom surface. The sample 300 to be tested is a metal anode. The sample 300 to be tested is placed in the detection container 100, and the air cathode sheet 400 is placed outside the detection container 100. A first opening 141 is opened on one side of the detection container 100, and its opening height is the same as the height of the sample 300 to be tested in the detection container 100. The air cathode sheet 400 is arranged outside the first opening 141. For the convenience of description, the side with the first opening 141 is defined as the first end surface 140, and the side opposite to the first end surface 140 is defined as the second end surface 150. The width direction of the detection container 100 is the flow direction of electrons between the metal anode and the air cathode sheet 400, and the length direction of the first end surface 140 is perpendicular to the width direction. Further, the other two opposite sides of the detection container 100 are named as the first side surface 160 and the second side surface 170 respectively.
[0036] The evaluation device further includes a clamping plate 110 whose distance from the first end face 140 of the container to be tested is adjustable. A second opening 113 is provided at the center of the clamping plate 110. The second opening 113 is of the same size as the first opening 141 of the first end face 140 and is opposite in position. Further, a connecting block 180 is provided on the first side face 160 and the second side face 170 of the container to be tested. A connecting screw 111 passes through the clamping plate 110 and the connecting block 180. A fastening nut 112 is provided at the end of the connecting screw 111. The distance between the clamping plate 110 and the first end face 140 is adjusted by adjusting the position of the fastening nut 112 on the connecting screw 111. The air cathode sheet 400 is placed between the clamping plate 110 and the first end, especially close to the first opening 141 and the second opening 113. Preferably, there are two connecting screws 111, which extend from both sides of the length direction of the second opening 113 to the two connecting blocks 180 on the first side face 160 and the second side face 170, respectively. There are preferably four fastening bolts, which are installed in groups of two at both ends of the two connecting screw rods 111 respectively.
[0037] like Figure 3 to Figure 5 As shown, the sample 300 to be tested is detachably mounted inside the detection container 100 through the support 120, and the support 120 with the sample 300 to be tested is preferably plugged into the inner wall of the first side surface 160 and the second side surface 170 in a keyway connection manner. Specifically, the support 120 includes a strip seat 125 extending along the length direction of the first end surface 140 and a clamping portion 124 fixed on the strip seat 125, and the clamping portion 124 has a through hole to accommodate the sample 300 to be tested. At least one boss 123 is also fixed on the strip seat 125, and the boss 123 extends along the width direction of the container to be tested, and a limiting groove 122 is provided on the boss 123. The gas collecting funnel 200 is inverted above the sample 300 to be tested, and its edge is placed in the limiting groove 122 of the boss 123, so that the gas collecting funnel 200 completely covers the sample 300 to be tested and remains stable during the gas collection process. There are preferably two bosses 123, which are respectively arranged on both sides of the clamping portion 124 to improve the installation stability of the gas collecting funnel 200. A mounting key 121 is also fixedly arranged on one side of the boss 123 away from the clamping portion 124. The mounting key 121 is vertically arranged on the strip seat 125 and cooperates with the mounting groove 130 on the first side 160 and the second side 170 to install or remove the sample 300 to be tested.
[0038] Further, the gas collecting funnel 200 includes a gas collecting portion and a gas guiding portion connected to each other, the gas collecting portion is a cone, and the gas guiding portion is a cylinder. The gas collecting funnel 200 is inverted above the support 120, and the edge of the gas collecting portion is embedded in the limit groove 122 of the support 120. In order to collect hydrogen during the discharge of the metal-air battery, a conical cut 210 is provided on the surface of the gas collecting portion corresponding to the position of the first opening 141, and the cross-sectional shape of the conical cut 210 is a hyperbolic cross-section. Further, a diaphragm 220 is covered on the conical cut 210, and the diaphragm 220 is preferably a PP film or a PE film to allow the ions participating in the reaction to pass freely during the discharge process while preventing hydrogen from escaping from the side of the funnel, thereby collecting the hydrogen released by the metal anode due to self-corrosion during the discharge process in the gas collecting funnel 200. Further, an alkaline burette is connected to the outlet end of the gas guiding portion, and the liquid level change of the alkaline burette is the hydrogen evolution data of the sample 300 to be tested.
[0039] When using the self-corrosion rate evaluation device for the anode material of a metal-air battery provided by the utility model, firstly, the air cathode sheet 400 is placed between the first end face 140 of the container to be tested and the clamping plate 110, and the connecting screw 111 and the fastening nut 112 are adjusted to clamp the air cathode sheet 400, so that the air cathode sheet 400 is directly opposite to the first opening 141 and the second opening 113. Then, the sample 300 (metal anode) to be tested is placed in the support 120, and further placed in the detection container 100. The gas collecting funnel 200 is turned upside down above the sample 300 (metal anode) to be tested, and the electrolyte solution is poured into the detection container 100, and the air cathode sheet 400, the sample 300 (metal anode) to be tested are connected to the discharge device through a wire, and finally the alkaline burette is installed on the top of the gas collecting funnel 200. After the device is installed, the discharge test of the sample 300 (metal anode) to be tested is started. The liquid level data in the alkaline burette is continuously recorded at a certain interval, and the hydrogen evolution rate can be calculated according to the amount of hydrogen evolved.
[0040] The self-corrosion rate evaluation device for metal-air battery anode materials provided by the utility model is used to evaluate the cast Mg-0.6% Gd alloy and the extruded Mg-0.6% Gd alloy respectively. The operation steps are as follows:
[0041] 1. The size of the sample used for the discharge performance test is 10mm×10mm×5mm (length*width*height). During the experiment, only the surface to be tested is exposed, and the other surfaces are inlaid with resin. The size of the test surface is 10mm×10mm, and the solution used is 3.5wt.% NaCl solution. The experimental sample is also polished with 400#, 600#, 800#, 1000# and 1200# water sandpaper until the sample surface is smooth without obvious scratches, rinsed with alcohol and blown dry with cold air for use.
[0042] 2. Place the mounted sample in the clamping part 124, with the surface to be tested facing the air cathode sheet 400, and completely cover the sample 300 to be tested with the inverted gas collecting funnel 200. Then, cover the top of the gas collecting funnel 200 with an alkaline burette, continuously record the liquid level data in the alkaline burette at a certain interval, and calculate the hydrogen evolution rate and corrosion rate according to the following formula:
[0043] Hydrogen evolution rate V H (mL cm -2 d -1 ) is calculated as:
[0044] V H =(V b -V a ) / (A*t),
[0045] Among them, V b is the initial liquid level reading in mL; V a is the liquid level reading when immersion is completed, in mL; A is the area of the sample immersion surface, in cm 2 ; t is the soaking time, unit is d.
[0046] Since 1 mol of magnesium metal corrodes to generate 22.4 L of hydrogen, the hydrogen evolution rate V H (mL cm -2 d -1 ) can be converted into the lost mass, i.e., the weight loss rate W L (mg cm -2 d -1 ), and its calculation formula is:
[0047] W L =(W b -W a ) / (A*t)=1.085V H
[0048] Where Wb is the mass of the sample before immersion, in mg; Wa is the weight of the sample after immersion and removal of corrosion products, in mg; A is the area of the sample immersion surface, in cm 2 ; t is the soaking time, unit is d.
[0049] Corrosion rate P calculated from weight loss rate W (mm y -1 ) can be calculated by the following formula:
[0050] P W =3.65W L / ρ
[0051] Where ρ is the density of the metal material, in g cm-3 .
[0052] The experiment used magnesium alloy, whose density ρ is 1.74 g cm -3 , the corresponding corrosion rate P is calculated from the hydrogen evolution rate H (mmy -1 ), calculated by the following formula:
[0053] P H =3.65W L / ρ=2.10W L =2.279V H
[0054] Through the above experimental method and calculation formula, the hydrogen evolution results of cast Mg-0.6%Gd alloy and extruded Mg-0.6%Gd alloy are calculated, and the calculation results are as follows:
[0055] like Figure 6 , cast Mg-0.6%Gd alloy at 10mA cm -2 The hydrogen evolution rate after 180 min discharge at the current density V H =99.2 (mL cm -2 d -1 ), corrosion rate P H =226.0768(mm y -1 ).
[0056] like Figure 7 , extruded Mg-0.6%Gd alloy at 10mA cm -2 The hydrogen evolution rate after 360 min discharge at the current density V H =133.6 (mL cm -2 d -1 ), corrosion rate P H =304.4744(mm y -1 ).
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the utility model rather than to limit it. Although the utility model has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the technical solution of the utility model can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the utility model.
Claims
1. A self-corrosion rate evaluation device for anode materials of a metal-air battery, characterized in that: The invention comprises a detection container (100), wherein a sample to be detected (300) is placed in the detection container (100), a first opening (141) communicating with the outside is provided on a wall surface of the detection container (100) at a position corresponding to the position of the sample to be detected (300), and an air cathode sheet (400) is arranged on the outer wall of the detection container (100) in a manner of covering the first opening (141); The device also includes a gas collecting funnel (200) which is inverted above the sample to be tested (300), a conical cutout (210) is provided on the side of the gas collecting funnel (200) at a position corresponding to the first opening (141), and a diaphragm (220) is covered on the conical cutout (210).
2. The device according to claim 1, characterized in that: The detection container (100) is a box with an opening at the top. The first opening (141) is opened on one of the side surfaces of the detection container (100). The side surface with the first opening (141) is a first end surface (140). The air cathode sheet (400) is arranged outside the first end surface (140).
3. The device according to claim 2, characterized in that: The device also includes a clamping plate (110) whose distance from the first end surface (140) is adjustable, and the air cathode sheet (400) is arranged between the clamping plate (110) and the first end surface (140) and abuts against the two, wherein a second opening (113) is provided on the clamping plate (110) at a position opposite to the first opening (141) to connect the air cathode sheet (400) and the outside.
4. The device according to claim 3, characterized in that: The second opening (113) is disposed at the center of the clamping plate (110), and its size is the same as that of the first opening (141).
5. The device according to claim 1, characterized in that: The device also includes a support (120) detachably mounted inside the detection container (100), and the sample (300) to be tested is placed in the detection container (100) through the support (120), wherein the support (120) includes a clamping portion (124), and the clamping portion (124) has a through hole to accommodate the sample (300) to be tested.
6. The device according to claim 5, characterized in that: The support (120) further comprises a strip seat (125) extending along the length direction of the first end surface (140), the clamping portion (124) being fixedly arranged on the strip seat (125), and at least one boss (123) being fixedly arranged on the strip seat (125), the boss (123) extending along the width direction of the container to be tested to form a placement platform for placing the gas collecting funnel (200); wherein a limiting groove (122) is provided on the boss (123), and an edge of the gas collecting funnel (200) is embedded in the limiting groove (122).
7. The device according to claim 5, characterized in that: Two assembly keys (121) are vertically arranged at the two ends of the strip seat (125), and assembly grooves (130) matching with the assembly keys (121) are arranged on the inner walls of the first side surface (160) and the second side surface (170) of the detection container (100) adjacent to the first end surface (140).
8. The device according to claim 7, characterized in that: Two bosses (123) are fixedly arranged on the strip seat (125), and the two bosses (123) are respectively arranged between the clamping portion (124) and the two assembly keys (121).
9. The device according to claim 3, characterized in that: Two connecting blocks (180) are respectively fixed on the first side surface (160) and the second side surface (170) adjacent to the first end surface (140); two connecting screws (111) pass through the clamping plate (110) and the connecting blocks (180) respectively; four fastening nuts (112) are installed in pairs at both ends of the two connecting screws (111); and the distance between the clamping plate (110) and the first end surface (140) is adjusted by adjusting the position of the fastening nuts (112) on the connecting screws (111).
10. The device according to claim 1, characterized in that: The cross-sectional shape of the conical cut (210) is a hyperbolic cross-sectional shape perpendicular to the width direction of the detection container (100).
